Inside network perimeter security the definitive guide to firewalls, VPNs, routers, and intrusion detection systems - Northcutt, Stephen; Zeltser, Lenny; Winters, Scott; Kent, Karen; Ritchey, Ronald W. (Sams Publishing, 2005)
A guide to preventing network intrusions and defending against intrusions that manage to slip through your perimeter. This book has been updated to reflect changes in the security landscape, both in terms of vulnerabilities and defensive tools. It also covers intrusion prevention systems and wireless security